EXPLORING THE ESSENCE OF HOMO ISLAMICUS: A CASE STUDY OF STUDENTS IN MALANG, EAST JAVA - Trapsila, Aji Purba Trapsila; Firdaus, Dwi Hidayatul; Budiharjo, Anas (Ekonomi Islam, 2024)
This study examines the impact of Homo Islamicus behavior, as reflected by Maqāsid Sharia, on the quality of life among Muslim students in Malang, East Java. Using a sample of 110 students from Brawijaya University and Malang State University, Partial Least Squares (PLS) analysis was employed to analyze the data. The research found significant relationships between maintaining reason, soul, and descendants with students' quality of life while maintaining property did not significantly affect it. The study highlights the need for a balanced approach to Homo Islamicus behavior, with maintaining religion showing the lowest score among the Maqāsid variables. These findings suggest that to enhance quality of life, the implementation of Maqāsid Sharia must be comprehensive. The study contributes to understanding the dynamics of Homo Islamicus behavior and its implications for the well-being of Muslim students.